Workarounds that work : how to conquer anything that stands in your way at work - Bishop, Russell, 1950- (McGraw-Hill, 2011)
Break through the barriers to get things done! What's more frustrating than knowing how to do your job, working hard, making tough decisions . . . and not getting results because some system, procedure, bureaucratic detail, or difficult personality gets in the way? In Workarounds That Work , Huffington Post columnist Russell Bishop shows how to boost your productivity with a complete strategy for outmaneuvering anything that stands in your way. The key is to know which procedures and people you can circumvent without causing even greater problems for yourself or coworkers. Bishop provides valuable insight into the workarounds that often hide in plain sight, including: Bypassing key stakeholders who stand in the way Preventing malicious people from shooting down good ideas Handling misaligned leadership and unclear directions Working around other groups or "silos" whose goals are at odds with yours Managing the power plays going on above and around you By following the strategies in Workarounds That Work , you will not only get the results you need-you will also be perceived of as someone who can always be relied upon to get things done, no matter what obstacles stand in the way.